Use of {99m}Tc-HMPAO in Estimating the Antihypertensive Therapy Impact on the Cerebral Perfusion in Patients with Arterial Hypertension Associated with Diabetes Mellitus Type 2 - Efimova I. Y.; Belokopytova N. V.; Efimova N. Yu. Nataliya Yurievna; Lishmanov Yu. B. Yury Borisovich (Radiation Technologies in Medicine, 2015)
Title screen